Copyright law awareness and compliance in selected city libraries in Metro Manila - Abubakar, Ismael G., III.; Santos, Antonio M. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2009)
With the rapid pace of change brought about by technology such as the ability of individuals to transfer, copy and use information freely, and to have instant access to knowledge that would previously have been difficult to find, there is a need to conduct this particular study. There is a need to value one of the key responsibilities of information centers in the 21st century as they struggle to create an environment where the literary and artistic creations of countless authors and copyright holders must be protected from exploitation and misuse and at the same time continuously advocating the fair use doctrine. This study aimed to find out the degree of familiarity on the local copyright legislation among City librarians in eight (8) major cities in Metro Manila and their compliance with it. Furthermore, it divided the cities into their respective districts and made use of a descriptive survey. A preliminary evaluation was done on almost all of the qualified libraries around the region before distributing the survey forms which allowed the proponent to limit the respondents with regards to the size/population of the city, the location, and the number of respondents in each library. The distribution of forms were done in two (2) weeks and the librarians were allotted a week to finish answering the questions. After gathering the findings, tabulation of the data followed containing brief explanation for each one. From the results, it was learned that majority of the respondents or 51 were moderately aware of the law. High levels of awareness were noted mostly from 21 of the librarians in the Southern Manila District than in the other areas. Not one of them was found out to be unacquainted about the law at the same time no one was identified to be fully aware of it. In evaluating the respondents on the occurrence of copyright problems encountered, 60 of them said that they experience copyright problems 1-2 times every six (6) months. The percentage of the frequency is very high in comparison to 26 of the respondents who said that their libraries never experience copyright problems. The three (3) most predominant problems encountered by the respondents in the implementation of the copyright law was: (1) Request for a single reproduction of a book, which had 70 of the responses, (2) Request to photocopy a portion of a thesis without the author's consent, about 60, and (3) Request to photocopy an entire book by a researcher from another institution, which roughly measured 21 of the answers. This study is of utmost importance as it can be a clear reminder for libraries to establish copyright policies and effectively implement these within the libraries. The findings from this study may perhaps create a significant impact in the use of information from its creation and distribution to its utilization and preservation.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Copyright -- Philippines; Public libraries -- Philippines -- Manila Metropolitan Area